Passions, affections, emotions and feelings - Fiorin, José Luiz (2008)
In this paper, I discuss whether emotions, affections, passions and feelings occupy the same theoretical place, or whether they occupy different ones. After showing how Semiotics develops interest in the problematic of passions, and how the approach to the states of soul evolved, I make an excursion through the etimology of the words ?affection?, ?passion?, ?emotion? and ?feeling? in order to detect the meanings that they progressively acquired. I show that they are synonyms [in relation to] their original meanings, but they are not synonyms when they gain specialized meanings. After stating that there are no perfect synonyms, I establish a distinction among those words in the framework of Tensive Semiotics, and state that their study is concerned with the same problematic of descriptive values, but especially with modal and aspectual values, which are correlated by their tensive valence. Keywords: Passions. Affections. Modality. Aspectuality. Tensivity.